(3GdMUf GdMUjf ef cdGe SjO GdeQSdjfs - (3eMeO Hf eMeO Hf eMeO Hf Ydj Hf jhSa, CHh GdNjQ, TeS GdOjf, GdYeQj GdOeTbqj Ke GdTjQGRj GdTGaYqj, GdTgjQ HGHf GdLRQj,(B833 (3g`s ((3eMeO Hf eMehO Wg s)
(3ChdgG (B:s
(3Gddge Udi Ydi SjO GdNdb eMeO hGdg hUMHg hHYO bGd GdabjQ (B: (3aEf gPG GdMUf GdMUjf ef cdGe SjO GdeQSdjf hcGf Udi Gddg Ydjg hSde jbhd (B: (3eG JQjO abdJ (B: (3jG QShd Gddg COY Gddg dMO hddeSdejf s
(3BNQgG (B:s
(3Gddge Udi Ydjg cdeG Zad Yf PcQg GdZGadhf hSde JSdjekG cKjQkG Gddge HMb YfOc CQaY Yf GdNdb eG fRd Hge hdG JSdW Ydjge ef dGjQMege jG QMje jG CQMe GdQGMejf s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B669s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs